Erving Goffman on Misinformation and Information Control: The Conduct of Contemporary Russian Information Operations. Issue 4 (14th June 2022) - Innes, Martin; Dawson, Andrew
Abstract : Misinformation is a social problem increasingly, and routinely, commanding significant political and public attention. Less well known is that Erving Goffman was writing about misinformation as early as 1953 in his PhD thesis. Subsequent to which, he wrote repeatedly about the social organization and conduct of "information control" across several of his most influential publications. This article distils his ideas about these concepts to explore how they illuminate the contemporary phenomena of misinformation. To do this, empirical data are introduced from a large‐scale research program exploring the causes, communication, and consequences of digital information operations and campaigns, with a particular focus upon the Internet Research Agency and Instagram. The analysis attends in particular to sequences of "revealing moves" and "concealing moves" performed by the social media account operators. The dialogue between the data and Goffman's concepts outlines the precepts of a sociologically inflected, interactionist position on misinformation.